Geological and Geophysical Factors Constraining the Occurrence of Earthquake Precursors in Geofluids: A Review and Reinterpretation - Martinelli, Giovanni; Tamburello, Giancarlo (Frontiers in Earth Science, 2020)
In this paper, we update the previous compilations of observed earthquake precursors from the published scientific literature of the last decade. We collected the epicentral coordinates, magnitude, hypocentral depth of each earthquake and the distance from the observed precursor and its time lag. The locations are reported and compared with data concerning geological and geophysical parameters like global seismicity, volcanic locations, heat flow and tectonic regimes. Possible relations between geological and geophysical parameters and the occurrence of fluid-related earthquake precursors are considered and discussed. Some geological and geophysical conditions can be deemed responsible for the occurrence of fluid-related earthquake precursory phenomena. Geophysical models used to explain the occurrence of earthquake precursors are discussed with the purpose of contributing to engineering proper monitoring networks. Areas of the world potentially suitable for earthquake fluid-related precursor monitoring are suggested.